2012
DOI: 10.33899/rden.2012.65065
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Candida albicans to Flexi-ble Denture Base Material

Abstract: Aims: Assessment of Candida albicans adherence to flexible denture base material (Valplast) and conventional heat polymerized acrylic resin in the presence and absence of saliva. Materials and Methods: A total of 28 square specimens (10 mm x10 mm x3mm) were constructed from Valplast and acrylic denture base materials according to manufacturers' instructions and kept without finishing or polishing. C. albicans was isolated from patients with denture stomatitis. Fourteen specimens (7 of each material) were not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
0
0
0
3
Order By: Relevance
“…Injectable acrylics are available in pre-mixed cartridges, whereas in the traditional technique, the powder and liquid are mixed by hand, which can cause air bubbles to remain in the material, resulting in increased surface roughness [23]. The adhesion of C. albicans to injectable acrylic materials was found to be lower than that of conventional acrylic resins [24], which is consistent with our research results. However, Young et al reported that the adhesion of C. albicans to injectable acrylic materials was not significantly different from that of conventional and autopolymerized acrylic resins [25].…”
Section: Discussionsupporting
confidence: 89%
“…Injectable acrylics are available in pre-mixed cartridges, whereas in the traditional technique, the powder and liquid are mixed by hand, which can cause air bubbles to remain in the material, resulting in increased surface roughness [23]. The adhesion of C. albicans to injectable acrylic materials was found to be lower than that of conventional acrylic resins [24], which is consistent with our research results. However, Young et al reported that the adhesion of C. albicans to injectable acrylic materials was not significantly different from that of conventional and autopolymerized acrylic resins [25].…”
Section: Discussionsupporting
confidence: 89%
“…Menurut beberapa studi yang dilakukan di universitas dan rumah sakit, 65% dari pe-makaian denture memiliki masalah yang disebabkan oleh C. albicans (yang merupakan spesies Candida paling banyak dijumpai) [4]. C. albicans dapat melakukan penetrasi pada nilon termoplastik dan tumbuh pada permukaan gigi tiruan sehingga dapat menginfeksi jaringan lunak dan merupakan penyebab terjadinya denture stomatitis [2].…”
Section: Pendahuluanunclassified
“…Perlekatan C. albicans pada basis gigi tiruan nilon termoplastik dipengaruhi oleh beberapa faktor seperti kekasaran permukaan, sifat kimia, sifat fisik dan sifat hidrofobik dari nilon termoplastik itu sendiri [4]. Kekasaran permukaan nilon termoplastik bisa didapatkan karena sifatnya yang sukar dipulas [14].…”
Section: Metode Penelitianunclassified
See 1 more Smart Citation
“…The silver-based antibacterial agent was used in denture base materials [8] to evaluate the distribution and manner of release of silver ions from the base [9,10]. Yeast of the type candida is commonly present in the plaque, their adhesion to the surface of the denture [11]. May cause candidosis infection to the patient and Surface roughness (irregularities on the surface) of the denture base material increases the likelihood of bacterial buildup and candida adherence compared to a smooth surface.…”
Section: Introductionmentioning
confidence: 99%